IMPLEMENTASI KODE ETIK PUSTAKAWAN BERDASARKAN STANDAR IPI BAGI PROFESI PUSTAKAWAN DI PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI IMAM BONJOL PADANG - Titin Tri Andini; Malta Nelisa (ADIBA : JOURNAL OF EDUCATION, 2023)
This study aims to describe (1) the basic attitude of librarians, (2) the relationship between librarians and librarians, (3) the relationship between librarians between librarians, (4) the relationship between librarians and libraries, (5) the relationship between librarians and professional organizations, (6) the relationship between librarians with society. This type of research is qualitative research using descriptive methods. The informants in this study were 8 librarians. Data analysis starts from the data reduction stage or selecting data that is considered important and grouping the data according to indicators, data presentation stage, and conclusion drawing stage. The results of this study indicate that First, the basic attitude of librarians has been carried out well which can be seen from the results of research conducted by librarians who have provided the needs of users and are responsible for the work done where librarians have worked in accordance with the rules that apply in the library. Second, librarians have fulfilled librarian relations with users well based on a code of ethics based on IPI standards where librarians protect the privacy rights of users and also provide information needs to users properly. Third, librarians have carried out librarian relations between librarians well where librarians carry out sharing activities with other librarians to improve competence and performance in the library. Fourth, the relationship between librarians and libraries has not been carried out properly where librarians are still rarely active in formulating policies in the library. Fifth, the relationship between librarians and professional librarian organizations has joined professional librarian organizations such as IPI but has not fully contributed. Sixth, the relationship between librarians and the community has not been carried out optimally where librarians rarely cooperate with the community.